Association between atopic dermatitis and race from infancy to early childhood: a retrospective cohort study. (11th August 2021) - Monir, Reesa L.; Schoch, Jennifer J.; Garvan, Cynthia W.; Neu, Josef; Lemas, Dominick J.
Abstract: Background: Atopic dermatitis (AD) is a common pediatric skin condition with significant morbidity. It is unclear what factors contribute to racial differences in disease prevalence. Methods: A single‐site, retrospective cohort study of infants born from June 1, 2011, to April 30, 2017, was performed. Results: Of the 4016 infants included, 39.2% ( n = 1574) were Black, 38.5% ( n = 1543) White (non‐Hispanic), 7.1% ( n = 286) Hispanic, 5.3% ( n = 213) Asian, 6.5% ( n = 262) "other" race, 3.4% ( n = 135) multiracial, and 0.1% ( n = 3) not reported. Prevalence of AD differed by race, with 37.0% ( n = 583) of Black, 25.8% ( n = 55) of Asian, 24.1% ( n = 69) of Hispanic, 23.0% ( n = 31) of multiracial, 19.1% ( n = 50) of "other" race, and 17.9% ( n = 276) of White patients diagnosed ( P < 0.0001). Delivery mode, NICU stay, and gestational age were all significantly associated with race. In modeling AD with logistic regression, race was significantly associated with the development of AD ( P < 0.0001, OR Black = 2.6 [2.2‐3.2], OR Asian = 1.6 [1.1‐2.2], OR Hispanic = 1.4 [1.0‐1.9], OR multiracial 1.4 [0.91‐2.2], OR "other" 0.97 [0.67‐1.4], and OR White 1.0). Conclusions: Racial differences in rates of AD arise early in life. Diagnosis is associated with race rather than delivery mode, insurance type, and gestational age. Further investigation into these disparities and interventions to mitigate them should focus on infancy and early childhood.